UNDERSTANDING LEVEL OF TABLIGH JAMAAT MEMBERS AT AN-NAHL Verse 125 (Case Study at Mosque of al-Falah II Jl. Sumatra Pekanbaru) - Jani Arni (Jurnal Ushuluddin, 2015)
This study studied the level of understanding of the Tabligh congregation members about the letter of al-Nahl verse 125 which contains about methods in preaching. Tabligh Jamaat is one group of Muslims who could be called active in proselytizing. They were proselytizing door to door or directly into the homes of Muslims to invite to goodness. Da’wah in the congregation sermons made by all members, because they think that the task of the mission is not only clerical duties. Al-Qur’an as a book of guidance has explained how the procedures or methods in carrying out da’wah. In Surat al-Nahl verse 125 explained that there are three methods of da’wah; bil hikmah, al-mau’izhah al-hasanah, and jadilhum billati hiya ahsan.From research conducted found that the level of understanding and practice of members of Tabligh congregation was very varied; some have a good understanding and practice, there are less in understanding the verses about methods of da’wah but its practices is good, as well as small part that have a poor understanding and its practice